Trajectories and influencing factors of psychological distress in nasopharyngeal carcinoma patients receiving radiotherapy (incorporating genetic factors): a multicenter longitudinal study - Ning, Jiajie; Huang, Jianhua; Liao, Yan; Long, Jianxiong; Zeng, Pingping (Frontiers in Oncology, 2025)
BackgroundThis multicenter longitudinal study seeks to investigate the dynamic changes of psychological distress (PD) in nasopharyngeal carcinoma (NPC) patients during radiotherapy, and reveal the expression profiles and regulatory networks of circRNAs in these NPC patients.Methods282 newly diagnosed NPC patients from three hospitals in China were included. Participants completed questionnaires and provided blood samples. PD trajectories were identified via a latent class growth model (LCGM). Moreover, the factors that influence the PD trajectories were explored. Whole transcriptome sequencing was performed to investigate genetic factors. The real-time quantitative PCR was applied to validate circRNAs. We predicted the target miRNAs, target mRNAs and target RNA-binding proteins (RBPs) of the top 10 malregulated circRNAs. Subsequently, circRNA-miRNA-mRNA (ceRNA) and circRNA-RBP networks were constructed. In addition, the role of circRNA and target mRNA parent genes was predicted by KEGG and GO analysis.ResultsLCGM identified two of the most important PD trajectories during radiotherapy in NPC patients: Class 1 “decline distress group” (11.0%) and Class 4 “rise distress group” (20.3%). Household monthly per capita income, coping strategies, and perceived social support emerged as important predictors of PD trajectories. Regarding genetic factors, 600 circRNAs and 123 miRNAs were identified as being significantly differentially expressed. Notably, hsa_circ_0004277 demonstrated significant differences between patients in the rise and decline distress groups (P < 0.01). ceRNA and RBP networks may influence the pathophysiology of PD in NPC patients undergoing radiotherapy.ConclusionThis study unraveled that PD trajectories in NPC patients during radiotherapy were heterogeneous, indicating the need for screening and timely interventions within this population. Furthermore, the expression patterns of ceRNA and circRNA–RBP networks and pathways related to these networks suggested a potential role of circRNAs in developing PD among NPC patients receiving radiotherapy.